Neglected fishery data sources as indicators of pre‐industrial ecological properties of Mediterranean swordfish (Xiphias gladius, Xiphiidae). Issue 4 (9th March 2022) - MacKenzie, Brian R.; Addis, Piero; Battaglia, Pietro; Consoli, Pierpaolo; Andaloro, Franco; Sarà, Gianluca; Nielsen, Anders; Romeo, Teresa
Abstract: Management of fish populations and ecosystems suffers from data and knowledge gaps, particularly with respect to how humans and nature affect dynamics at multi‐decadal and longer time scales. However, collection of new data which indicates population or ecosystem status is slow and expensive. Here we analyse c. 110 years of neglected fishery data for an overexploited top predator, swordfish, in the Mediterranean Sea. These data are available at scales of high time–space–biological resolution (i.e., sub‐weekly, sub‐regional sea; individual weights) and allow different ecological questions to be addressed than is possible with coarsely scaled data (e.g., annually resolved total catches aggregated over large sea areas). We constructed regional indicators of population status (relative abundance, mean individual size and its variability, migration phenology) covering most of the 20th century, and pre‐dating other population datasets by 50–70 years. The length and duration of these new time series allowed detection of significant multi‐annual/decadal variations in abundance and mean weight not detectable in shorter, more recent time series. These new data and evidence of multi‐annual variability in population variables improve knowledge of Mediterranean swordfish ecology. The findings provide a new basis on which further historical data recovery and analysis of contemporary data can provide new perspectives and opportunities for quantifying vulnerability of populations to exploitation and climate change.